Respostas

2014-05-16T23:06:30-03:00
x² + 6x - 7 = 0
a = 1
b = 6
c = -7
       Δ = b² - 4ac
       Δ = 6² - 4 . 1 . (-7)
       Δ = 36 + 28
       Δ = 64
                x = - b ± √Δ / 2a
                x = - 6 ± √64 / 2 . 1
                x' = - 6 - 8 / 2 = -14 / 2 = -7
                x'' = - 6 + 8 / 2 = 2 / 2 = 1
As raízes da equação são -7 e 1.
            
x² - 8x + 15 = 0
a = 1
b = -8
c = 15
        Δ = b² - 4ac
        Δ = (-8)² - 4 . 1 . 15
        Δ = 64 - 60
        Δ = 4
               x = - b ± √Δ / 2a
               x = - (-8) ± √4 / 2 . 1
               x' = 8 - 2 / 2 = 6 / 2 = 3
               x'' = 8 + 2 / 2 = 10 / 2 = 5
As raízes da equação são 3 e 5.

x² - 7x + 12 = 0
a = 1
b = -7
c = 12
        Δ = b² - 4ac
        Δ = (-7)² - 4 . 1 . 12
        Δ = 49 - 48
        Δ = 1
               x = - b ± √Δ / 2a
               x = - (-7) ± √1 / 2 . 1
               x' = 7 - 1 / 2 = 6 / 2 = 3
               x'' = 7 + 1 / 2 = 8 / 2 = 4
As raízes da equação são 3 e 4.

Espero ter ajudado. Valeu!
1 5 1